2019
DOI: 10.3390/ijerph16214259
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Model-Based Programme to Promote Personal and Social Responsibility and Its Effects on Motivation, Prosocial Behaviours, Violence and Classroom Climate in Primary and Secondary Education

Abstract: The present study aimed to apply a programme based on Hellison’s Teaching Personal and Social Responsibility model (TPSR), traditionally used in Physical Education, to other school subjects and analyse aspects related to motivation and satisfaction of basic psychological needs among other variables. The programme was applied for 7 months during one academic year, all students receiving at least 60% of the lessons through this teaching methodology. A mixed method research methodology and quasiexperimental desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 32 publications
(40 reference statements)
14
64
1
1
Order By: Relevance
“…On the other hand, no improvements were found in the violence perception, despite the fact that former studies in the PE field, such as [55][56][57][58], related higher responsibility and sportsmanship levels with lower violence and disruptive behavior levels. In line with the present work, similar results have been already obtained without changes in the violence perception in the study by Manzano-Sánchez and Valero-Valenzuela [54], where, despite the decrease in antisocial behavior, there was no change in the student violence perception who received the TPSR program. It should be noted that the same results were also reported in studies focused only on the PE field, where it was found that personal and social responsibility is capable of negatively predicting attitudes of violence, but where the intervention study that was associated with it did not find decreases in this variable [21].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…On the other hand, no improvements were found in the violence perception, despite the fact that former studies in the PE field, such as [55][56][57][58], related higher responsibility and sportsmanship levels with lower violence and disruptive behavior levels. In line with the present work, similar results have been already obtained without changes in the violence perception in the study by Manzano-Sánchez and Valero-Valenzuela [54], where, despite the decrease in antisocial behavior, there was no change in the student violence perception who received the TPSR program. It should be noted that the same results were also reported in studies focused only on the PE field, where it was found that personal and social responsibility is capable of negatively predicting attitudes of violence, but where the intervention study that was associated with it did not find decreases in this variable [21].…”
Section: Discussionsupporting
confidence: 93%
“…With regard to the basic psychological needs satisfaction, improvements were obtained in autonomy and competence, as well as in the psychological mediators' index. These results are positive and are in line with those found by Manzano and Valero-Valenzuela [53], who achieved improvements in the only basic psychological need measured, which was autonomy, and with Manzano-Sánchez and Valero-Valenzuela [54], who found improvements in the psychological mediators index for both primary and secondary school students. Some research in the PE field, when they applied the TPSR, obtained higher values in all, [32] or at least in some of them [57].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These programs have had very positive results (Ruiz et al, 2006;Caballero et al, 2013;Gordon and Doyle, 2015;Sánchez-Alcaraz et al, 2016;Andrew et al, 2018). The benefits go beyond an overall improvement in students' social responsibility, also obtaining positive effects in the motivation, prosocial behaviors, reduction of violent behaviors, or improvements in the classroom climate (Manzano-Sánchez and Valero-Valenzuela, 2019). This can even be the basis of trauma-informed practice (TIP), aimed at ensuring the physical and emotional safety of disadvantaged students (Ellison et al, 2019).…”
Section: Introductionmentioning
confidence: 99%